2014
DOI: 10.3389/fnhum.2014.00673
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial task context makes short-latency reaches prone to induced Roelofs illusion

Abstract: The perceptual localization of an object is often more prone to illusions than an immediate visuomotor action towards that object. The induced Roelofs effect (IRE) probes the illusory influence of task-irrelevant visual contextual stimuli on the processing of task-relevant visuospatial instructions during movement preparation. In the IRE, the position of a task-irrelevant visual object induces a shift in the localization of a visual target when subjects indicate the position of the target by verbal response, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…Furthermore, a temporal delay between stimulus presentation and action performance can influence the weighting of egocentric and allocentric information with stronger weighting of allocentric information for delayed than immediate movements (Bridgeman, Peery, & Anand, 1997;Chen, Byrne, & Crawford, 2011;Hay & Redon, 2006;Obhi & Goodale, 2005). Importantly, allocentric information is also incorporated in immediate reaches as recently demonstrated by a study on the Roelofs effect (Taghizadeh & Gail, 2014) and as we demonstrated in our experiments. Since allocentric coding is supposed to be stronger for delayed than immediate reaches (Bridgeman et al, 1997;Chen et al, 2011;Hay & Redon, 2006;Obhi & Goodale, 2005), the allocentric weights we observed here could have even been higher with a temporal delay before the reach.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, a temporal delay between stimulus presentation and action performance can influence the weighting of egocentric and allocentric information with stronger weighting of allocentric information for delayed than immediate movements (Bridgeman, Peery, & Anand, 1997;Chen, Byrne, & Crawford, 2011;Hay & Redon, 2006;Obhi & Goodale, 2005). Importantly, allocentric information is also incorporated in immediate reaches as recently demonstrated by a study on the Roelofs effect (Taghizadeh & Gail, 2014) and as we demonstrated in our experiments. Since allocentric coding is supposed to be stronger for delayed than immediate reaches (Bridgeman et al, 1997;Chen et al, 2011;Hay & Redon, 2006;Obhi & Goodale, 2005), the allocentric weights we observed here could have even been higher with a temporal delay before the reach.…”
Section: Discussionsupporting
confidence: 77%
“…While several studies support the hypothesis that illusions do not affect the visual control of action, but only affect perception and memory-guided actions (e.g., Aglioti et al, 1995;Bridgeman et al, 1997;Westwood et al, 2000), other studies have found evidence against this hypothesis (e.g., Brenner and Smeets, 1996;Franz et al, 2009;Taghizadeh and Gail, 2014). For example, the Müller-Lyer illusion not only changes the perceived length of a line by its inward or outward pointing arrowheads, but can also change the amplitude of pointing movements and saccadic eye movements along its shaft (e.g., Binsted and Elliott, 1999;Post and Welch, 1996) 1 .…”
Section: Introductionmentioning
confidence: 95%
“…However, allocentric information also crucially contributes to spatial coding for action. For example, although the presence of landmarks results in more accurate and less variable reaches in both online and delayed movement tasks (Krigolson & Heath, 2004;Obhi & Goodale, 2005), cue-irrelevant background information can lead to spatial distortions of pointing or reaching movements (Diedrichsen, Werner, Schmidt, & Trommershäuser, 2004;Taghizadeh & Gail, 2014). Further studies could show that the main factors driving the influence of allocentric information are landmark stability, as well as its reliability as a cue (Byrne & Crawford, 2010;Camors, Jouffrais, Cottereau, & Durand, 2015).…”
Section: Introductionmentioning
confidence: 99%